Staging romance across the Channel: French–English exchanges and generic common ground. Issue 1 (July 2019) - Hillman, Richard
This article explores a number of neglected cross-connections between English romantic drama from about 1585 to 1615, notably including Shakespeare's last plays, and the French tragicomic tradition as it evolved prior to and beyond these dates. I suggest that dramatic and non-dramatic French models played a considerable part alongside Italian ones in stimulating development of what might be termed 'tragedy with a happy ending' in England, and that English texts, in turn, fed back into French practice. Attention is given to the precedent for key aspects of Pericles provided by François de Belleforest's version of the Apollonius of Tyre romance.